What is the nett benefit of a gravity circuit? - McGrath, Teresa; Staunton, William(Bill); Bax, Alan (2017)
The Curtin University Gold Technology Group has been involved in surveying, modelling and optimisation of batch centrifugal concentrator (BCC) type gravity circuits and CIP/CIL circuits for nearly two decades. The most commonly asked question regarding gravity recovery is, “What is the benefit of a gravity circuit”, which can be hard, if not impossible, to quantify. With the help of the AMIRA P420 Project’s Integrated Liberation Leach Model (ILLM) it is now possible to evaluate the affect of gravity recovery on total gold recovery when changes are made to the grind size, gravity and/or leach/adsorption circuits. This paper demonstrates how the ILLM can be used to determine the nett benefit of introducing or modifying a gravity circuit and assess the effect of operating conditions (grind size, coarse gold size distribution, leach residence time, carbon activity, etc.) on plant performance.